Пасивні системи вентилювання в енергоощадних будинках - Мізерник, Василь Андрійович; Mizernyk, Vasyl Andriiovych (Національний університет "Львівська політехніка", 2024)
У даній магістерській кваліфікаційній роботі бралось до уваги дослідження процесів природнього повітрообміну в енергоощадних будівлях за допомогою пасивної вентиляції з використанням сонячного димоходу, а також був проведений дослід з використанням аеродинамічної труби для того, аби провести аналіз пасивної вентиляції з використанням димоходу та провітрювачів під дією вітрової сили. Актуальність обраної тематики обумовлена необхідністю зниження енергоспоживання у будівельній галузі та переходом до сталого розвитку, що вимагає впровадження енергоефективних технологій без втрати рівня комфорту для користувачів.

This master's qualification work took into account the study of natural air exchange processes in energy-saving buildings using passive ventilation using a solar chimney, and an experiment using a wind tunnel was also conducted to analyze passive ventilation using a chimney and ventilators under the influence of wind force. The relevance of the chosen topic is due to the need to reduce energy consumption in the construction industry and the transition to sustainable development, which requires the implementation of energy-efficient technologies without losing the level of comfort for users.
Passive ventilation systems in energy-efficient houses
Keywords: 3.192.00.00; пасивна вентиляція; конвекція; сонячний димохід; термомодернізація. Метою даної роботи є експериментальне та чисельне дослідження ефективності роботи пасивної вентиляційної системи на основі сонячного димоходу для покращення повітрообміну в умовах помірного клімату. Для дослідження було обрано місто Львів. Для досягнення поставленої мети були сформульовані наступні завдання: визначити показники руху повітря у робочій зоні моделі; здійснити порівняльний аналіз ефективності вентиляції; змоделювати роботу сонячного димоходу у фізичній моделі та програмному середовищі Energy2D; а також виконати економічну оцінку впровадження пасивної системи вентиляції. У роботі застосовано два основні методи дослідження: фізичне моделювання в аеродинамічній трубі лабораторії та комп’ютерне моделювання в середовищі Energy2D. Фізичне моделювання є одним з найважливіших етапів дослідження ефективності роботи пасивної вентиляційної системи. У межах даної магістерської кваліфікаційної роботи було виконано серію експериментів на зменшеній моделі приміщення; яка була виготовлена в масштабі 1:25. Модель була встановлена у спеціалізованій аеродинамічній трубі; що дозволило створити кероване середовище для аналізу поведінки повітряного потоку в умовах; максимально наближених до реальних. Основною метою фізичного моделювання було визначення швидкості потоку повітря в межах робочої зони приміщення. Для цього в контрольних точках моделі проводились вимірювання повного тиску; які згодом використовувалися для розрахунку динамічного тиску та швидкості повітря. Під час експериментів враховувалися такі фактори; як: • інтенсивність потоку повітря в трубі; • наявність та розташування вхідних і вихідних вентиляційних каналів; • зміна тиску у верхній частині димоходу. Аеродинамічна труба дозволила отримати наочні результати; які відображають поведінку повітря у приміщенні за умови роботи димоходу. Моделювання в Energy 2 D дозволило візуалізувати процеси теплообміну та руху повітря у приміщенні з пасивною вентиляційною системою. Віртуальне середовище Energy2D забезпечило змогу оперативно змінювати геометричні параметри моделі; інтенсивність сонячного випромінювання; розташування вхідних та вихідних отворів; а також температурні умови; що дало змогу провести серію порівняльних експериментів. Моделювання дозволило детально дослідити; як змінюється розподіл температури в приміщенні під впливом сонячного нагріву та як формується конвекційний потік повітря у межах робочої зони. Об’єктом дослідження є процеси природної вентиляції повітря в житлових і громадських приміщеннях; що забезпечуються за допомогою пасивних вентиляційних систем; зокрема сонячних димоходів. Предметом дослідження є аеродинамічні характеристики природної вентиляції; які виникають під дією температурних і тискових градієнтів у пасивних системах повітрообміну; зокрема у сонячному димоході. Метою дослідження є експериментальне та теоретичне обґрунтування ефективності роботи пасивної вентиляційної системи на основі сонячного димоходу шляхом моделювання повітряного потоку в робочій зоні приміщення; змодельованого в масштабі; з використанням аеродинамічної труби. Результати дослідження підтвердили; що при відповідному конструктивному вирішенні сонячний димохід здатен забезпечити стабільну циркуляцію повітря; яка відповідає нормам повітрообміну для житлових та адміністративних будівель. Практичне значення отриманих результатів полягає у можливості використання отриманих даних для проектування нових будівель з пасивною вентиляцією або модернізації існуючих вентиляційних систем з метою підвищення енергоефективності; Passive ventilation; convection; solar chimney. The aim of this work is an experimental and numerical study of the efficiency of a passive ventilation system based on a solar chimney to improve air exchange in temperate climate conditions. The city of Lviv was chosen for the study. To achieve this goal; the following tasks were formulated: to determine the air movement indicators in the working area of the model; to carry out a comparative analysis of ventilation efficiency; to simulate the operation of a solar chimney in the physical model and the Energy2D software environment; and to perform an economic assessment of the implementation of a passive ventilation system. The work used two main research methods: physical modeling in a laboratory wind tunnel and computer modeling in the Energy2D environment. Physical modeling is one of the most important stages of studying the efficiency of a passive ventilation system. Within the framework of this master's qualification work; a series of experiments were performed on a reduced model of the room; which was made on a scale of 1:25. The model was installed in a specialized wind tunnel; which allowed creating a controlled environment for analyzing the behavior of the air flow in conditions as close as possible to real ones. The main goal of physical modeling was to determine the air flow velocity within the working area of the room. For this; total pressure measurements were taken at the control points of the model; which were subsequently used to calculate the dynamic pressure and air velocity. During the experiments; the following factors were taken into account: • air flow intensity in the pipe; • the presence and location of the inlet and outlet ventilation ducts; • pressure change in the upper part of the chimney. The wind tunnel allowed us to obtain visual results that reflect the behavior of the air in the room when the chimney is operating. Modeling in Energy 2 D allowed us to visualize the processes of heat exchange and air movement in a room with a passive ventilation system. The Energy2D virtual environment provided the opportunity to quickly change the geometric parameters of the model; the intensity of solar radiation; the location of the inlet and outlet openings; as well as temperature conditions; which made it possible to conduct a series of comparative experiments. The modeling allowed us to study in detail how the temperature distribution in the room changes under the influence of solar heating and how the convection air flow is formed within the working area. Particular attention was paid to the analysis of the efficiency of the solar chimney - it was shown that even with moderate heating by solar energy; a stable air flow arises; capable of providing natural ventilation. The object of the study is the processes of natural air ventilation in residential and public premises; provided by passive ventilation systems; in particular solar chimneys. Special attention is paid to the study of the behavior of the air flow in the working area; simulated in a wind tunnel. The subject of the study is the aerodynamic characteristics of natural ventilation; which arise under the influence of temperature and pressure gradients in passive air exchange systems; in particular in a solar chimney. The aim of the study is to experimentally and theoretically substantiate the efficiency of a passive ventilation system based on a solar chimney by modeling the air flow in the working area of a room modeled to scale using a wind tunnel. The results of the study confirmed that with an appropriate design solution; the solar chimney is able to provide stable air circulation that meets the air exchange standards for residential and administrative buildings. In addition; a comparative analysis with mechanical ventilation showed that the passive system allows for reduced operating costs; which is a significant argument in favor of its implementation in modern design. The practical significance of the results is the possibility of using the obtained data for the design of new buildings with passive ventilation or the modernization of existing ventilation systems in order to increase energy efficiency